2016
DOI: 10.1073/pnas.1616400113
|View full text |Cite
|
Sign up to set email alerts
|

One low-dose exposure of gold nanoparticles induces long-term changes in human cells

Abstract: We report the in vitro long-term (20 wk) changes in cells exposed to well-characterized gold nanoparticles (Au NPs) with varying shapes and surface coatings under both chronic (exposure to Au NPs continuously over 20 wk) and nonchronic (initial acute cell exposure to Au NPs, followed by 20 wk in NP-free cell media) conditions. Both chronic and nonchronic Au NPs exposures at low dose induce modifications at the gene level after long periods. In attempt to overcome from the injuries caused by nanoparticle exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
143
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 50 publications
(61 reference statements)
4
143
0
Order By: Relevance
“…However it was recently shown that cells exposed to low doses of various gold nanoparticles with 'biocompatible' surfactants induce genetic changes over a long period of time [347]. This particularly resulted in the upregulation of genes associated with oxidative stress and apoptosis (amongst others) for a single (non-chronic) dose, which is the typical approach for SERS measurements.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…However it was recently shown that cells exposed to low doses of various gold nanoparticles with 'biocompatible' surfactants induce genetic changes over a long period of time [347]. This particularly resulted in the upregulation of genes associated with oxidative stress and apoptosis (amongst others) for a single (non-chronic) dose, which is the typical approach for SERS measurements.…”
Section: Challengesmentioning
confidence: 99%
“…Whilst the phototoxicity directly from the excitation source will be low, the localized hot-spot intensity is necessarily large, which could induce a variety of unwanted/damaging reactions in a complex cellular environment over time. Despite the recent in vivo studies using mouse models, it will still be difficult to envisage approval for clinical applications of SERS on humans in the near-future without (SERS-specific) long-term studies, in a similar manner to Falagan et al [347]. It is therefore more likely to see ex vivo and solution-based SERS techniques achieving success in medical applications.…”
Section: Challengesmentioning
confidence: 99%
“…Moreover, these changes surprisingly lasted over 20 weeks. 39 Therefore, we predict the persistent accumulation of Au-NPs in the body organs could present similar toxicological responses. We emphasize that exploring the cytotoxicity of Au-NPs in extended long-term studies rather than solely investigating their acute short-term responses will not only elucidate more information about their safety profile, but also help to design safer Au-NPs for nanomedicine.…”
Section: Gold and Silver Npsmentioning
confidence: 88%
“…In addition, degradation of Au-NPs could result in formation of smaller particles that are known to be toxic, as previously mentioned. Falagan-Lotsch et al 39 explored the long-term effect of exposing wellcharacterized Au-NPs to human dermal fibroblasts in vitro and found that even a single exposure of a subcytotoxic dose of Au-NPs could change the expression of genes that are associated with oxidative stress and inflammation. Moreover, these changes surprisingly lasted over 20 weeks.…”
Section: Gold and Silver Npsmentioning
confidence: 99%
“…The toxicity of NPs has consequently been studied extensively and has been the subject of detailed reviews. [61][62][63][64][65] Briefly, the toxicity and biocompatibility of NPs is largely dependent on their size, shape, charge and surface chemistry, [66][67][68][69] as well as other factors such as their propensity to aggregate. 70 Each of these properties must be carefully considered when designing nanosensors for in vivo applications and toxicological effects must be assessed when fabricating or altering probes for bioanalysis.…”
mentioning
confidence: 99%